Teachers’ continuous improvement & learning: a professional development program grounded on the principles of adult learning, contextualized in professional learning communities (PLCs), and bolstered by the literature of biography-driven instruction (BDI) - Fabre Merchán, Paolo Geovanny (Kansas State University, 2021)
Teachers’ continuous improvement and its impact on student academic achievement has been the focus of initiatives and efforts toward reform and research throughout the history of education, particularly in the late twentieth and early twenty-first century. The purpose of this study was to examine whether a professional development program grounded on the principles of adult learning, contextualized in professional learning communities (PLCs), and bolstered by the literature of biography-driven instruction (BDI), yields a statistically significant change in teachers’ self-efficacy, as measured by the Teachers’ Self-Efficacy Scale (TSES), associated with the three factors of effective teaching: student engagement, instructional strategies, and classroom management. An extensive review of relevant literature detailed in chapter two offered a more robust composite theoretical framework for the challenge addressed within this study and a best explanatory model for teachers’ continuous improvement and learning. This study was framed by a quasi-experimental control-experiment group design. An Ecuadorian context was purposively chosen as the setting for this study, including a sample of 30 tenured teachers from the College of Education of an educational institution. The data was collected using Qualtrics with an online version of the TSES. The data analysis was conducted through a one-way Multivariate Analysis of Variance (MANOVA) using the SPSS software, with an alpha score of .05. The results obtained from the quantitative data collection and analysis supported the researcher in rejecting the null hypothesis. The results of this study contribute to the literature of adult learning, PLCs, and BDI and also suggest areas for future research, including quantitative and qualitative research designs. The findings of this study are related and consist with relevant literature, confirming that a program contextualized in PLCs exhibits a positive change in teachers’ self-efficacy as measured by TSES. Learning during adulthood requires a collaborative learning environment that guides people to explore, activate, share, and critically reflect on their experiences through inquiry-dialogue. Finally, bolstered by the literature of BDI, the finding of this study permitted to advocate for humanizing teacher education based on a collaborative adult-centered learning environment. Professional development is not only about the instructional process, strategy, or content; it should be a vehicle that wakes up the curiosity of learning and the desire to be more effective when guiding students to personal and academic success, impacting teachers at professional and personal levels.
Keywords: Teachers’ continuous improvement; Adult learning; Professional learning communities; Biography-driven instruction; Self-efficacy; Professional development